Open vs. closed reduction combined with minimally invasive plate osteosynthesis in humeral fractures. Issue 4 (3rd July 2016) - Liu, Yin-Wen; Wei, Xiao-En; Kuang, Yong; Zheng, Yu-Xin; Gu, Xin-Feng; Zhan, Hong-Sheng; Shi, Yin-Yu
Abstract: Aim To explore a more effective surgical procedure, the outcomes of closed manipulative reduction (CMR) combined with minimally invasive plate osteosynthesis (MIPO) and conventional open reduction and internal fixation (ORIF) for treating proximal humeral fractures were compared.Material and methods In a retrospective study of patients operated for humerus shaft fractures from April 2008 to July 2011, the outcomes of 33 patients treated with CMR/MIPO were compared with the outcomes of 42 patients treated with ORIF. The fractures were classified, and the incision length, blood transfusion, operating time, as well as the VAS (Visual Analog Scale) pain scores were analyzed. The neck–shaft angles of the proximal humerus were detected, and the postoperative function of the shoulder was evaluated.Results The mean values of incision length, blood transfusion, and VAS pain scores at the 1st and 3rd day after CMR/MIPO and operation time were lower than that of ORIF. The postoperative radiographs verified good position of all screws and satisfactory bone fracture reduction in both groups. Meanwhile, in the ORIF group, nonunion (three cases) and humeral head necrosis (four cases) were detected.Conclusions The MR/MIPO technique showed smaller incisions, easier operation, less blood transfusion and more effective recovery of shoulder joint function for treating proximal humeral fractures than ORIF.